FACTORS RELATED TO SUBJECTIVE COGNITIVE DECLINE AND COGNITIVE IMPAIRMENT AMONG OLDER ADULTS IN KOREA. (11th November 2018) - Lee, J; Sung, J; Choi, M
Abstract: Cognitive function is essential for independent life in older adults. Cognitive impairment is not a part of healthy ageing, and it disturbs individuals' quality of life as well as daily life. Subjective cognitive decline (SCD) is one of the common health problems in the older adults. However, less is known about relationship between SCD, cognitive function and related factors. This study used a descriptive cross-sectional design to identify risk factors of SCD and cognitive function of older adults in Korea. A convenience sample of 182 patients was recruited at a senior welfare center in Seoul, Korea. Demographic characteristics, comorbidities, depression, level of physical and cognitive activity, instrumental activities of daily living, SCD and cognitive function were measured with a structured questionnaire. Student t-tests, Chi-square tests, and hierarchical multiple regressions were utilized in statistical analysis. Among the 182 participants, 64.3% were female. The mean age was 78.4 ± 5.91 years. The findings in this study showed that 37.4% among total participants were not cognitively intact. Depression, perceived health status and cognitive function were associated with SCD (F=7.10, p<.001, adjusted R 2 =25.3). Age, education level, perceived health status and SCD were related with cognitive function (F=20.98, p<.001, adjusted R 2 =47.0). After controlling these variables, cognitive activity was independently related to cognitive function (F=19.57, p<.001, R 2 =.50.8). These results suggest that cognitive activity should be encouraged to maintain cognitive function. In addition, people who complain SCD and have risk factors such as depression at an early stage are crucial to prevent actual cognitive decline through therapeutic interventions.